Some Notes on Ideal Output - Wright, David McCord (Quarterly Journal of Economics, 1962)
Introduction, 173. — I. “Pure” versus “perfect” competition, 173. — II. “Pure but imperfect” competition, 175. — III. Growth, competition and full employment, 176. — IV. Equilibrium versus dynamic analysis, 178. — V. Pure versus monopolistic competition in a multidisturbance world, 183. — VI. Conclusion, 184.